The relationship between professional identity and academic burnout among music education students: The mediating role of academic self-efficacy - Ye Zhu (Acta Psychologica)
Background: Academic burnout is a common mental health issue among college students, particularly pronounced among students majoring in music education. Despite evidence that professional identity influences academic burnout, the mechanism of action remains unclear, particularly the relationship between academic self-efficacy and academic burnout. Furthermore, research specifically addressing the connection between professional identity and academic burnout among music majors is relatively limited. Based on the theoretical framework of academic self-efficacy, this study constructs a mediation model to explore whether academic self-efficacy mediates the relationship between professional identity and academic burnout. Methods: This study employed a questionnaire-based research method, selecting music education undergraduates at Zhengzhou Normal University as participants. A total of 731 questionnaires were collected after randomly selecting participants, and 701 valid responses were retained after excluding invalid questionnaires. The study was measured using the College Students' Professional Identity Questionnaire, the Academic Burnout Scale and the Academic Self-Efficacy Scale. Correlation analysis and mediation effect analysis were conducted using SPSS 26.0. Result: The study found that professional identity was negatively correlated with academic burnout, and academic self-efficacy played a partial mediating role in this relationship. Higher professional identity was associated with higher academic self-efficacy, which in turn effectively reduced the level of academic burnout. Conclusion: Enhancing professional identity can strengthen academic self-efficacy, thereby alleviating academic burnout among music education undergraduates. These findings provide important theoretical foundations and practical implications for future educational interventions and mental health support.